Diabetes risk score in the United Arab Emirates: a screening tool for the early detection of type 2 diabetes mellitus. Issue 1 (29th March 2018) - Sulaiman, Nabil; Mahmoud, Ibrahim; Hussein, Amal; Elbadawi, Salah; Abusnana, Salah; Zimmet, Paul; Shaw, Jonathan
Abstract : Objective: The objective of this study was to develop a simple non-invasive risk score, specific to the United Arab Emirates (UAE) citizens, to identify individuals at increased risk of having undiagnosed type 2 diabetes mellitus. Research design and methods: A retrospective analysis of the UAE National Diabetes and Lifestyle data was conducted. The data included demographic and anthropometric measurements, and fasting blood glucose. Univariate analyses were used to identify the risk factors for diabetes. The risk score was developed for UAE citizens using a stepwise forward regression model. Results: A total of 872 UAE citizens were studied. The overall prevalence of diabetes in the UAE adult citizens in the Northern Emirates was 25.1%. The significant risk factors identified for diabetes were age (≥35 years), a family history of diabetes mellitus, hypertension, body mass index ≥30.0 and waist-to-hip ratio ≥0.90 for males and ≥0.85 for females. The performance of the model was moderate in terms of sensitivity (75.4%, 95% CI 68.3 to 81.7) and specificity (70%, 95% CI 65.8 to 73.9). The area under the receiver-operator characteristic curve was 0.82 (95% CI 0.78 to 0.86). Conclusions: A simple, non-invasive risk score model was developed to help to identify those at high risk of having diabetes among UAE citizens. This score could contribute to the efficient and less expensive earlier detection of diabetes in this high-risk population.